2014
DOI: 10.1155/2014/727496
|View full text |Cite
|
Sign up to set email alerts
|

Titanium Dioxide as a Catalyst Support in Heterogeneous Catalysis

Abstract: The lack of stability is a challenge for most heterogeneous catalysts. During operations, the agglomeration of particles may block the active sites of the catalyst, which is believed to contribute to its instability. Recently, titanium oxide (TiO 2 ) was introduced as an alternative support material for heterogeneous catalyst due to the effect of its high surface area stabilizing the catalysts in its mesoporous structure. TiO 2 supported metal catalysts have attracted interest due to TiO 2 nanoparticles high a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
200
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(206 citation statements)
references
References 206 publications
(354 reference statements)
1
200
0
5
Order By: Relevance
“…[21,29] Briefly, TiCl3 was added drop wise into a boiling 0.7 mol dm -3 HCl solution, to obtain the TiCl3 solution of 21.5 g dm -3 . During 90 min boiling under reflux, a part of the TiO2 particles, generated in the reaction mixture, aggregated in a loose precipitate.…”
Section: Tio2 Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…[21,29] Briefly, TiCl3 was added drop wise into a boiling 0.7 mol dm -3 HCl solution, to obtain the TiCl3 solution of 21.5 g dm -3 . During 90 min boiling under reflux, a part of the TiO2 particles, generated in the reaction mixture, aggregated in a loose precipitate.…”
Section: Tio2 Synthesismentioning
confidence: 99%
“…TiO2 appears to be suitable replacement since it is at least of low cost and high stability. [21][22][23] The synthesis of Pt/TiO2 needs to be carefully tailored to meet the demands for promising electrocatalytic materials of the next generation, especially for the cathodic FC reactions. [4] It was found that TiO2 enhances the Pt activity for oxygen reduction reaction [24] , which is assigned to increased electron density on Pt due to partial charge transfer from oxide to metal nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Titania has also received attention as a catalyst support that possesses good mechanical resistance, strong metal support interaction, chemical stability, and acid-base property and high potential in photocatalyst-related applications [27]. The deposition of titania on the surface of Fe 3 O 4 @SiO 2 was obtained following a different method [28].…”
Section: Post-coating Process: Magnetic Supports Containing Ceria Timentioning
confidence: 99%
“…Titanium is the most common oxide in heterogeneous catalysis and photo-catalysis for the purification gas and liquid media from toxicant [1,2]. This fact is attributed to the fairly high chemical stability under different operating conditions, no toxicity, and relatively low cost of this material.…”
Section: Introductionmentioning
confidence: 99%